Matrix-graded and fibre-steered composites to tackle stress concentrations. (1st January 2019) - Stanier, David; Radhakrishnan, Arjun; Gent, Ian; Roy, Sree Shankhachur; Hamerton, Ian; Potluri, Prasad; Scarpa, Fabrizio; Shaffer, Milo; Ivanov, Dmitry S.
Abstract: This paper studies the feasibility of improving structural performance of composites in the presence of stress concentrators. Matrix grading through local deposition of additive-enhanced matrices and fibre steering by varying fibrous architecture are examined independently and in combination on a glass-fibre triaxial braided composite subjected to open hole tensile test. Stiffened and toughened matrices were incorporated through precise point-wise injections of liquid reactive resin into dry preforms (Liquid Resin Printing). Fibre steering was implemented by varying the braiding angle along the length of the braided sleeve. It has been shown that these novel forms of architecture modification enable a significant improvement in composite strength through a variety of deformation mechanisms. This includes local stiffening of composite in the direct vicinity of the stress concentrator and damage accumulation away from the stress concentrators. The experimental observations are explained by using simple finite-element models.